Autoimmunity and immune system dysregulation in schizophrenia: IgGs from sera of patients hydrolyze myelin basic protein. Issue 2 (15th August 2018) - Parshukova, Daria; Smirnova, Liudmila P.; Ermakov, Evgeny A.; Bokhan, Nikolay A.; Semke, Arkadiy V.; Ivanova, Svetlana A.; Buneva, Valentina N.; Nevinsky, Georgy A.
Abstract: Several different theories of schizophrenia (SCZ) were discussed; the causes of this disease are not yet clear. Using ELISA, it was shown that titers of autoantibodies against myelin basic protein (MBP) in SCZ patients are ~1.8‐fold higher than in healthy individuals but 5.0‐fold lower than in patients with multiple sclerosis. Several rigid criteria were checked to show that the MBP‐hydrolyzing activity is an intrinsic property of SCZ IgGs. Approximately 82% electrophoretically homogeneous SCZ IgGs purified using several affinity sorbents including Sepharose with immobilized MBP hydrolyze specifically only MBP but not many other tested proteins. The average relative activity of IgGs from patients with negative symptoms was 2.5‐fold higher than that of patients with positive symptoms of SCZ, and it increases with the duration of this pathology. It was shown that abzymes are the earliest statistically significant markers of many autoimmune pathologies. Our findings surmise that the immune systems of individual SCZ patients can generate a variety of anti‐MBP abzymes with different catalytic properties, which can attack MBP of the myelin‐proteolipid shell of axons. Therefore, autoimmune processes together with other mechanisms can play an important role in SCZ pathogenesis. MBP‐hydrolyzing antibodies were previously detected in the blood of 80% to 90% of patients with systemic lupus erythematosus (SLE) and multiple sclerosis (MS). In addition, some similar neuropsychiatric indicators of disease common to SLE, MS, and SCZ were described in the literature. Thus, the destruction of the myelin sheath and the production of MBP‐hydrolyzing antibodies can be a common phenomenon for some different diseases. Abstract : Our findings surmise that the immune systems of schizophrenia patients can generate a variety of abzymes hydrolyzing myelin basic protein (MBP), attacking MBP of the myelin‐proteolipid shell of axons. Several rigid criteria were checked to show that the MBP‐hydrolyzing activity is an intrinsic property of schizophrenia IgGs. Approximately 82% homogeneous IgGs purified using several affinity sorbents including MBP‐Sepharose hydrolyze specifically only MBP (A, lanes 1 ad 2) but not many other tested proteins (B and C).